Análisis de estrategias de producción audiovisual utilizadas por los profesionales de Comunicación Social en la ciudad de Babahoyo para mejorar la calidad de su trabajo - Contreras Jimenez, Edgar Jefferson (2020)
In this case study, the different audiovisual production strategies used by social communication professionals in the city of Babahoyo to improve the quality of their work are analyzed, through concepts, stages and procedures whose purpose is to investigate the methods that these professionals they use to create their audiovisual content. The quality of an audiovisual work is represented by the experience acquired throughout their professional career, this leads to generating strategies that benefit the communicator to develop as a producer with a great performance of audiovisual work, and generating interest to the consumer therefore it must be constantly prepared. Using production tools and applied theories, a communicator can generate audiovisual content with a clear and precise idea, this allows him to convey a concept that he wants to show through images or videos, making his main idea known to the viewer. Using various research methods such as: interviews and direct observation, we reveal how professionals show us their various anecdotes about what a production is about, the tools they use and what their experience was when creating an audiovisual and the strategies they were forming throughout their professional life.